2019
DOI: 10.1002/cyto.a.23903
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Analysis of Hematopoietic Populations in Rat Bone Marrow. Impact of Trauma and Hemorrhagic Shock

Abstract: Severe injury and hemorrhagic shock (HS) result in multiple changes to hematopoietic differentiation, which contribute to the development of immunosuppression and multiple organ failure (MOF). Understanding the changes that take place during the acute injury phase may help predict which patients will develop MOF and provide potential targets for therapy. Obtaining bone marrow from humans during the acute injury phase is difficult so published data are largely derived from peripheral blood samples, which infer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Bone marrow stroma failed to grow to confluence by day 14 in >90% of trauma patients. These data indicate that trauma induces a bone marrow dysfunction that releases immature white blood cells into circulation and may also contribute to a failure to clear infection and an increased propensity to organ failure (123,124). Moreover, in pathophysiological conditions such as trauma, a partial blockade in the differentiation of immature myeloid cells into mature myeloid cells results in an expansion of this population called myeloid-derived suppressor cells (MDSCs), which have remarkable ability to suppress T-cell responses and to modulate macrophage cytokines (125).…”
Section: Bone Marrow Dysfunctionmentioning
confidence: 99%
“…Bone marrow stroma failed to grow to confluence by day 14 in >90% of trauma patients. These data indicate that trauma induces a bone marrow dysfunction that releases immature white blood cells into circulation and may also contribute to a failure to clear infection and an increased propensity to organ failure (123,124). Moreover, in pathophysiological conditions such as trauma, a partial blockade in the differentiation of immature myeloid cells into mature myeloid cells results in an expansion of this population called myeloid-derived suppressor cells (MDSCs), which have remarkable ability to suppress T-cell responses and to modulate macrophage cytokines (125).…”
Section: Bone Marrow Dysfunctionmentioning
confidence: 99%
“…In rodent models of hemorrhagic shock, it has been demonstrated that, in addition to suppressive neutrophil mobilization, there is an increase in hematopoietic progenitor cell (HPC) mobilization from the bone marrow, which may serve to modulate the inflammatory response to hemorrhage ( Francis et al., 2019 ; Xiang et al., 2012 ). In fact, injection of bone marrow-derived hematopoietic stem cells (HSCs) has been shown to decrease mortality and organ dysfunction in response to cecal ligation and puncture ( Mei et al., 2010 ; Nemeth et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not examine the bone marrow. Since both cells of the monocyte‐macrophage lineage and B cells are generated in the bone marrow after birth, flow cytometric analysis of hematopoietic (myeloid or lymphoid) populations in the bone marrow may also be useful in rats (Francis et al, 2019 ) Future studies may be considered to determine the effects of bpV(pic) on immune cells including macrophages and B cells in the bone marrow. Finally, although our data support the notion that bpV(pic) induces activation of Akt through inhibition of PTEN, we have no data for Akt activity with or without bpV(pic) in LV and fat tissue of stressed and nonstressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, inhibition of PTEN by bpV(pic) ameliorated LV and AT pathology in DS/obese rats subjected to restraint stress. Such amelioration was likely mediated by two key mechanisms: (Baumgarth, 2011 ) reduced blood pressure and promotion of coronary capillary formation via activation of a PI3K–Akt–HIF‐1α–VEGF–eNOS/NO pathway, resulting in suppression of LV inflammation, fibrosis, and diastolic dysfunction and (Francis et al, 2019 ) alteration of the distribution of immune cells in AT, without a change in fat mass, induced by activation of PI3K–Akt signaling, and resulting in attenuation of AT inflammation. Further studies are warranted to uncover the precise molecular mechanisms underpinning these actions of PTEN inhibition in MetS associated with stress.…”
Section: Discussionmentioning
confidence: 99%